Ginsenoside Rb1 Alleviates Alcohol-Induced Liver Injury by Inhibiting Steatosis, Oxidative Stress, and Inflammation - Lai, Yuqi; Tan, Qinxiang; Xv, Shu; Huang, Sha; Wang, Yuhua; Li, Yunjia; Zeng, Ting; Mo, Chan; Chen, Yuyao; Huang, Shaohui; Zhou, Chuying; Gao, Lei; et al. (Frontiers in Pharmacology, 2021)
Alcoholic liver disease (ALD) has become a heavy burden on health worldwide. Ginsenoside Rb1 (GRb1), extracted from Panax quinquefolium L., has protective effects on many diseases, but the effect and mechanisms of GRb1 on ALD remain unknown. This study aimed to investigate the protective effects of GRb1 on ALD and to discover the potential mechanisms. Zebrafish larvae were exposed to 350 mM ethanol for 32 h to establish a model of acute alcoholic liver injury, and the larvae were then treated with 6.25, 12.5, or 25 μM GRb1 for 48 h. The human hepatocyte cell line was stimulated by 100 mM ethanol and meanwhile incubated with 6.25, 12.5, and 25 μM GRb1 for 24 h. The lipid changes were detected by Oil Red O staining, Nile Red staining, and triglyceride determination. The antioxidant capacity was assessed by fluorescent probes in vivo, and the expression levels of inflammatory cytokines were detected by immunohistochemistry, immunofluorescence, and quantitative real-time PCR. The results showed that GRb1 alleviated lipid deposition in hepatocytes at an optimal concentration of 12.5 μM in vivo. GRb1 reversed the reactive oxygen species accumulation caused by alcohol consumption and partially restored the level of glutathione. Furthermore, GRb1 ameliorated liver inflammation by inhibiting neutrophil infiltration in the liver parenchyma and downregulating the expression of nuclear factor-kappa B pathway-associated proinflammatory cytokines, including tumor necrosis factor-α and interleukin-1β. This study revealed that GRb1 has a protective effect on alcohol-induced liver injury due to its resistance to lipid deposition as well as antioxidant and anti-inflammatory actions. These findings suggest that GRb1 may be a promising candidate against ALD.